Comparative Constructions in Ray Bradbury's “The Martian Chronicles” - E. N. Sokolova (Научный диалог, 2025)
The aim of this study is to conduct a comprehensive analysis of comparative structures within the context of the author's individual stylistic approach. The research sources include the original text of Ray Bradbury's "The Martian Chronicles" and its Russian translation by L. L. Zhdanova. The material for analysis consists of 354 parallel textual fragments featuring comparative constructions. Methods employed in this study include comparative, contextual, and component analysis, as well as linguistic and cultural commentary and quantitative assessment. It is established that in L. L. Zhdanova's Russian translation of "The Martian Chronicles," there are 180 instances of equivalent translation of comparisons and 64 examples of comparative phrases translated through various transformations (generalization, specification, modulation, lexical addition, compression, descriptive translation). Attention is given to the identification of universal and culturally specific features within the linguistic worldview reflected in these comparisons. It is demonstrated that both subjects and objects of comparison, in the context of Bradbury's authorial perception, encompass humanity, artifacts, and nature. The identified models are illustrated with examples: wrists — icicles; face — apple; housewives — bears (HUMAN > NATURE); dwellings — snakes; city — lizard; shotguns — cranes; ships — petals; blouse — flower (ARTIFACT > NATURE), among others. Notably, there are 80 instances where comparisons are absent in the original but present in the translation, and 10 cases where comparative constructions are missing in the translation despite their presence in the original.